2023
DOI: 10.1007/s00592-023-02140-w
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery in individuals with type 2 diabetes is not associated with short or long-term risk of diabetic retinopathy progression: results from a nationwide cohort study

Abstract: Aims Bariatric surgery is used to induce weight loss and glycemic stability in type 2 diabetes (T2D). It has been a concern that this may lead to early worsening of diabetic retinopathy (DR) due to a rapid decline in HbA1c. In this study, we evaluated the risk of short and long-term DR development and need for ocular intervention in an entire nation of individuals with T2D undergoing bariatric surgery. Methods The study comprised a national, register-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…Secondly, the lack of a control group prevented us from determining the influence of bariatric surgery on DR. Supporting this notion, a recent study showed that bariatric surgery had no impact on the risk of developing DR in both the long and short term [49]. Thirdly, the short 1 year follow-up period may not fully capture the progressive nature of DR. Lastly, the change in DR severity between baseline and 1 year post-surgery was up to two years in some patients, which may affect the overall results.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the lack of a control group prevented us from determining the influence of bariatric surgery on DR. Supporting this notion, a recent study showed that bariatric surgery had no impact on the risk of developing DR in both the long and short term [49]. Thirdly, the short 1 year follow-up period may not fully capture the progressive nature of DR. Lastly, the change in DR severity between baseline and 1 year post-surgery was up to two years in some patients, which may affect the overall results.…”
Section: Discussionmentioning
confidence: 99%